The Clinical and Microbiological Effects of LANAP Compared to Scaling and Root Planing Alone in the Management of Periodontal Conditions - Edwin Sever Bechir (Diagnostics, 2023)
The purpose of this study was to evaluate the efficiency of two therapeutic procedures clinically and microbiologically in the management of periodontally affected teeth: scaling and root planing alone and the laser-assisted new attachment procedure (LANAP). Molecular biological determinations of bacterial markers through the polymerase chain reaction (real-time PCR) method with standard PET tests (species-specific DNA probes at a time) were used for the quantification of three of the most important periodontal pathogens (Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, and Treponema denticola). Both nonsurgical periodontal therapies were proven effective in patients with chronic periodontal disease; however, LANAP was associated with a greater reduction in pocket depth and improved clinical outcomes, associated with a significant decrease in the amount of Porphyromonas gingivalis. The clinical results included a decrease in periodontal pocket depth, bleeding on probing, and dental plaque, with LANAP having better overall outcomes than SRP alone. The use of Nd:YAG lasers in LANAP therapy is a safe and effective procedure that is well accepted by patients.